Microstip Antenna Reflection Coefficient with X Slot Addition Method for 5G Connection - Yessi Kartini Gultom; Syah Alam; Indra Surjati (Universitas Medan Area, 2022)
The development of cellular technology has now entered the 5th generation (5G), this 5th generation provides 3 types of services, eMBB (enhanced Mobile BroadBand), URLLC (Ultra-Reliable and Low-Latency Communications) and mMTC (massive Machine Type of Communications). One of the important devices in 5G technology is an antenna device which is able to support these 3 services. 5G technology requires an antenna that has high performance. There are various types of antennas, one of which is a microstrip antenna. Microstrip antenna is one of the most widely used antennas in telecommunications because of its light mass, small dimensions and easy fabrication. There are various ways or methods that can be done to overcome the narrow bandwidth of microstrip antennas, by increasing the thickness of the substrate, using parasitic elements, reducing the value of the dielectric constant, adding inserts to the feeder, or by modifying the patch by adding slots on the patch antenna. In this study to improve the performance value of the microstrip antenna, the researchers discussed increasing the reflection coefficient by adding X Slots to a microstrip antenna with a working frequency of 3.5 GHz for 5G communication. The results of this study showed an increase in the reflection coefficient of 67%, and an increase in bandwidth of 5%.